ISOPHLEBIID DRAGONFLIES FROM THE LATE MESOZOIC OF EASTERN TRANSBAIKALIA (ODONATA: ISOPHLEBIIDAE) - Pritykina L.N. (My University, 2006)
Based on the study of more than 300 isophlebiid specimens from several Late Mesozoic sites in eastern Transbaikalia (Ukurei, Tergen', Glushkovo, and Byankino formations), new genera and species are described: Xeta olovica, Dahurium draco, and Sinitsia sophiae. The insect-bearing deposits are dated Late Jurassic according to analysis of their odonatofauna. © Pleiades Publishing, Inc. 2006.
Keywords: ASIA; DRAGONFLIES; FAUNAL ASSEMBLAGES; ISOPHLEBIIDAE; JURASSIC; NEW TAXA; ODONATA; Mesozoic::Jurassic; Мезозой::Юрская